Oral health among adults aged ≥45 years in India: Exploring prevalence, correlates and patterns of oral morbidity from LASI wave-1 - Shishirendu Ghosal; Abhinav Sinha; Sushmita Kerketta; Ardhendu Sekhar Acharya; Srikanta Kanungo; Sanghamitra Pati (Elsevier, 2022)
Background: Burden of oral morbidities is adding up with ageing population. Management requires special knowledge and is often expensive. In India, oral health has become an ancillary component of health policies & insurance. Additionally, lack of nationally representative data necessitates recent evidence. We aimed to estimate the prevalence of oral morbidities, assess its correlates and patterns among older adults, followed by healthcare accessibility and utilization for the patients with oral health issues. Methods: A nationally representative sample of 65,562 individuals aged ≥45 years from Longitudinal Ageing Study in India (LASI), wave-1, formed the study population. Prevalence was reported as descriptive statistics with 95% confidence interval (CI). Multivariable logistic regression assessed the association between various covariates and oral morbidities. Further we did a pattern analysis to identify prevalent patterns of oral morbidities. Results: Oral morbidities were prevalent among 77.02% of the population, more among females (78.73%). Smoking was found to be significantly associated [AOR: 1.62 (1.45-1.82)] with oral morbidities. Loose teeth and missing teeth were the most prevalent dyad (6.12%). Only 3.16% participants had dental insurance. Just 2% of the study participants with oral morbidity, were willing to visit a dentist. Conclusions: This study is the first to report patterns of frequently occurring oral morbidities. The trends in healthcare utilisation and unmet needs among older adults, calls for a comprehensive oral health programme and a space in health policy identifying the Health and Wellness Centers as an ideal point of care.